Advances in sustainable manufacturing proceedings of the 8th Global Conference on Sustainable Manufacturing - Seliger, Günther; Khraisheh, Marwan K. 1968- (Marwan Kamal); Jawahir, I. S. (Springer, 2011)
Non-renewable materials can no longer be disposed once humankind's ever increasing needs cannot be fulfilled anymore due to limited resources. Reuse and recycling become inevitable requirements for product and process design. Renewable resources must not be consumed in quantities higher than can be regained. New technologies have to be developed and applied for a Sustainable Product Development and Life Cycle Engineering to fulfill the needs of humankind, protecting public health, welfare, and environment. The 8th Global Conference on Sustainable Manufacturing brings together some of the world?s leading experts to present a scientific conference in Abu Dhabi, one of the world?s fastest growing economies and a global leader in the development of sustainable technologies. The conference will focus on 7 areas: Value adding by sustainable manufacturing in the UAE Potentials of renewables Education for sustainability engineering Green supply chain and transportation Microelectronics and resource efficiency Technology driven startups Sustainable products and manufacturing processes.